Monitoring and Quantifying Burn Wounds on Pig Skin using Thermal Measurements (The International Journal of Engineering & Information Technology (IJEIT), 2016)
A new thermal method for detecting burnseverity or monitoring burn wound healing is presented. The thermal measurement method avoids the need forintroducing any substance or radiation to monitor bloodperfusion or detect the depth of burnt tissue. The method ofpredicting and monitoring burns was tested experimentallyby implementing four different burn severities on two pigsand monitoring the burns over five days. Averagedestimated thermal resistance and blood perfusion valueswere used to detect burn depth from thermalmeasurements. A damage function was introduced toillustrate those burns which cause third degree burns. The20 and 75-second burns were quantified as third degreeburns. The laboratory measured non-perfused layerscalibrates very well with the estimated burn depth from theperfusion-thermal resistance probe. This paper hasdemonstrated the ability of perfusion-thermal resistanceprobe to characterize burn severity